2008
DOI: 10.1182/blood-2008-03-148726
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B is a negative regulator of interleukin 4–induced STAT6 signaling

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a ubiquitously expressed enzyme shown to negatively regulate multiple tyrosine phosphorylation-dependent signaling pathways. PTP1B can modulate cytokine signaling pathways by dephosphorylating JAK2, TYK2, and STAT5a/b. Herein, we report that phosphorylated STAT6 may serve as a cytoplasmic substrate for PTP1B. Overexpression of PTP1B led to STAT6 dephosphorylation and the suppression of STAT6 transcriptional activity, whereas PTP1B knockdown or deficiency augmented IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 48 publications
2
82
0
Order By: Relevance
“…Moreover, our ChIP-seq data (supplemental Tables S2 and S3) revealed robust recruitment of GR and RNAPII to the PTPN1 locus. PTPN1 is a direct target of the STAT family that represses STAT-dependent responses to cytokines, including the asthma-associated cytokine, IL4 (11,81). We thus speculate that GR cooperatively regulates negative feedback responses to diverse inflammatory signals, providing a general mechanistic explanation for the broad potency of GCbased therapies in treating a multitude of immune-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our ChIP-seq data (supplemental Tables S2 and S3) revealed robust recruitment of GR and RNAPII to the PTPN1 locus. PTPN1 is a direct target of the STAT family that represses STAT-dependent responses to cytokines, including the asthma-associated cytokine, IL4 (11,81). We thus speculate that GR cooperatively regulates negative feedback responses to diverse inflammatory signals, providing a general mechanistic explanation for the broad potency of GCbased therapies in treating a multitude of immune-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Stat5 is also a substrate for Ptpn1, and Ptpn1 deficiency increases Stat6 phosphorylation in B cells (20,21). Additionally, Ptpn1-deficient mice suffer from systemic inflammation, increased leukocyte migration, and is a potential molecule in regulating the allergic response (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nigam et al (26) have observed that Although STAT6 activation in response to IL-4 and IL-13 has been well documented, the molecular mechanisms responsible for the termination of STAT6 signaling are largely unknown. Recently, protein-tyrosine phosphatases (PTP) have been shown to dephosphorylate STAT6 and act as negative regulators of IL-4/STAT6 signaling (27). STAT6 responses are also negatively regulated by SOCS1 (28).…”
Section: Discussionmentioning
confidence: 99%